Chenopodium polyploidy inferences from Salt Overly Sensitive 1 (SOS1) data. Issue 4 (1st April 2015) - Walsh, Brian M.; Adhikary, Dinesh; Maughan, Peter J.; Emshwiller, Eve; Jellen, Eric N.
Abstract : Premise of the study: Single‐copy nuclear loci can provide powerful insights into polyploid evolution. Chenopodium (Amaranthaceae) is a globally distributed genus composed of approximately 50–75 species. The genus includes several polyploid species, some of which are considered noxious agricultural weeds, and a few are domesticated crops. Very little research has addressed their evolutionary origin to date. We construct a phylogeny for Chenopodium based on two introns of the single‐copy nuclear locus Salt Overly Sensitive 1 ( SOS1 ) to clarify the relationships among the genomes of the allotetraploid and allohexaploid species, and to help identify their genome donors. Methods: Diploid species were sequenced directly, whereas homeologous sequences of polyploid genomes were first separated by plasmid‐mediated cloning. Data were evaluated in maximum likelihood and Bayesian phylogenetic analyses. Key results: Homeologous sequences of polyploid species were found in four clades, which we designate as A–D. Two distinct polyploid lineages were identified: one composed of American tetraploid species with A and B class homeologs and a second composed of Eastern Hemisphere hexaploid species with B, C, and D class homeologs. Conclusions: We infer that the two polyploid lineages arose independently and that each lineage may have originated only once. The American diploid, C. standleyanum, was identified as the closest living diploid relative of the A genome donor for American tetraploids, including domesticated C. quinoa, and is of potential importance for quinoa breeding. The east Asian diploid species, C. bryoniifolium, groups with American diploid species, which suggests a transoceanic dispersal.